(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
Quince is a pome fruit with limited world consumption, as such very few data are available about its pre and postharvest characteristics. The harvest time lasts from mid September to the middle of October based on the different cultivars. Quince fruit show a climacteric respiratory pattern. The fruit can be stored at 0 or 2ºC for two to six months and storage can be prolonged up to seven months by controlled atmo-sphere conditions of 2% O2+ 3% CO2 at 2ºC. The formation of flesh browning is the most limiting factor in storage of quince fruit. In this paper, some characteristics of quince fruit are reviewed